2015
DOI: 10.1111/anae.13082
|View full text |Cite
|
Sign up to set email alerts
|

TACR1 gene polymorphism and sex differences in postoperative nausea and vomiting

Abstract: SummaryWe hypothesised that the genetic effect of single nucleotide polymorphisms in the TACR1 gene, which encodes NK1 receptors, could influence the sex difference in postoperative nausea and vomiting. Thirty-two selected single nucleotide polymorphisms were genotyped by the Sanger sequencing method in 200 patients who underwent lower abdominal surgery. The incidence and severity of postoperative nausea and vomiting were evaluated after surgery. The rs3755468-SNP showed significant association with the incide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
22
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 59 publications
6
22
0
1
Order By: Relevance
“…Contrary to expectation, non-smoking status, history of motion sickness, nitrous oxide use, and surgery duration were not identi ed as risk factors in this study. This observation is consistent with results of our previous study in a different Japanese cohort [8]. Surprisingly, fentanyl concentration was also not a PONV risk factor.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Contrary to expectation, non-smoking status, history of motion sickness, nitrous oxide use, and surgery duration were not identi ed as risk factors in this study. This observation is consistent with results of our previous study in a different Japanese cohort [8]. Surprisingly, fentanyl concentration was also not a PONV risk factor.…”
Section: Discussionsupporting
confidence: 93%
“…Furthermore, the multiple logistic regression analysis indicated a strong association between rs11232965-SNP in MIR4300HG and female sex with PONV incidence (Table 4). Female sex per se was previously identi ed as the strongest PONV risk factor [2], and our current and previous results [8] con rm this (the odds ratios were 14.7-fold and 7.15-fold, respectively). Sex is a genetic trait, and we speculate sex differences in PONV may involve variable regulation by lncRNAs or transcription factors.…”
Section: Discussionsupporting
confidence: 83%
“…Nevertheless, rs1333114-SNP variation was not a statistically significant genetic factor in the multiple logistic regression analysis (Table 4) Furthermore, the multiple logistic regression analysis indicated a strong association between rs11232965-SNP in MIR4300HG and female sex with PONV incidence (Table 4). Female sex per se was previously identified as the strongest PONV risk factor [2], and our current and previous results [8] confirm this (the odds ratios were 14.7-fold and 7.15-fold, respectively). Sex is a genetic trait, and we speculate sex differences in PONV may involve variable regulation by lncRNAs or transcription factors.…”
Section: Ponvsupporting
confidence: 89%
“…Indeed, our previous study showed polymorphism in TACR1 located where estrogen may act as a transcription factor was associated with PONV incidence and severity. [8] In this study no similar female-associated sequences were identified near rs1333114-SNP in PTPRD or rs11232965-SNP in MIR4300HG. Contrary to expectation, non-smoking status, history of motion sickness, nitrous oxide use, and surgery duration were not identified as risk factors in this study.…”
Section: Ponvmentioning
confidence: 52%
See 1 more Smart Citation